2005
DOI: 10.1111/j.1475-6773.2005.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Quality Measure for Clinical Inertia in Diabetes Care

Abstract: Objective. To develop a valid quality measure that captures clinical inertia, the failure to initiate or intensify therapy in response to medical need, in diabetes care and to link this process measure with outcomes of glycemic control. Data Sources. Existing databases from 13 Department of Veterans Affairs hospitals between 1997 and 1999. Study Design. Laboratory results, medications, and diagnoses were collected on 23,291 patients with diabetes. We modeled the decision to increase antiglycemic medications at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 36 publications
8
88
2
1
Order By: Relevance
“…20,27,30 Berlowitz et al found that intensification of therapy was related to better blood pressure control 27 and that intensification of diabetes medications improved glycemic control over 2 years. 30 Additionally, Brown et al's study 20 found a peak in glycemic excursion prior to the addition of the metformin and that patients spent numerous months above target A1c before a therapeutic change was made. Straka et al 31 found that 70% of subjects who were above the LDL target of 100 mg/dl were not on lipid medications.…”
Section: Discussionmentioning
confidence: 99%
“…20,27,30 Berlowitz et al found that intensification of therapy was related to better blood pressure control 27 and that intensification of diabetes medications improved glycemic control over 2 years. 30 Additionally, Brown et al's study 20 found a peak in glycemic excursion prior to the addition of the metformin and that patients spent numerous months above target A1c before a therapeutic change was made. Straka et al 31 found that 70% of subjects who were above the LDL target of 100 mg/dl were not on lipid medications.…”
Section: Discussionmentioning
confidence: 99%
“…5 The inappropriate intensification of treatment to insulin therapy further affects glycemic control, has a direct impact on patient encounters, and may affect adherence to medications. [6][7][8][9][10] Earlier use of insulin in patients with type 2 diabetes has therefore been recommended by the European Association for the Study of Diabetes and the American Diabetes Association. 3 Delays in initiating insulin therapy may result from patients' psychological resistance to insulin, clinical inertia, or a combination thereof.…”
Section: Perceptions Of Usability and Design For Prefilled Insulin Dementioning
confidence: 99%
“…This threshold effect has been commonly observed in other similar studies. 30,35 Other factors that contribute to the threshold effect could be 'overestimation of current care' or 'complacency with borderline values' , leading to the physician's subjective misperception that the care provided is sufficient. 34 …”
Section: Discussionmentioning
confidence: 99%